2021
DOI: 10.3171/2021.9.focus21265
|View full text |Cite
|
Sign up to set email alerts
|

Spinal versus general anesthesia for minimally invasive transforaminal lumbar interbody fusion: implications on operating room time, pain, and ambulation

Abstract: OBJECTIVE There has been increasing interest in the use of spinal anesthesia (SA) for spine surgery, especially within Enhanced Recovery After Surgery (ERAS) protocols. Despite the wide adoption of SA by the orthopedic practices, it has not gained wide acceptance in lumbar spine surgery. Studies investigating SA versus general anesthesia (GA) in lumbar laminectomy and discectomy have found that SA reduces perioperative costs and leads to a reduction in analgesic use, as well as to shorter anesthesia and surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The most cited article had 1013 citations and was published in 1997 by Collins et al [ 6 ], followed by Chung et al [ 7 ] with 271 citations in 1997 and Sinatra et al [ 8 ] with 252 citations in 2005. The first two published articles were by Laitinen and Nuutinen [ 9 ] and Baker [ 10 ] in February 1992, and the most recent articles were published in December 2021 by De Biase et al [ 11 ] and Rajput et al [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most cited article had 1013 citations and was published in 1997 by Collins et al [ 6 ], followed by Chung et al [ 7 ] with 271 citations in 1997 and Sinatra et al [ 8 ] with 252 citations in 2005. The first two published articles were by Laitinen and Nuutinen [ 9 ] and Baker [ 10 ] in February 1992, and the most recent articles were published in December 2021 by De Biase et al [ 11 ] and Rajput et al [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies concluded significant benefits for length of stay and early recovery that were perhaps better explained by patient selection and expectation-setting than to effects of the anesthetic technique per se . More recently, awake spine surgery has expanded as a term in the surgical literature to refer to any patient undergoing spine surgery under regional anesthesia with or without regional analgesia, irrespective of level of sedation [8,13,14 ▪▪ ,18,19,22,23 ▪ ]. Indeed, the term is increasingly used interchangeably with neuraxial anesthesia, even in systematic reviews, which included RCTs comparing neuraxial anesthesia with sedation to general anesthesia and in population studies wherein details of sedation, if provided, are not captured [8,14 ▪▪ ].…”
Section: Comparative Anesthetic Technique and The Spine Surgeon: ‘Awa...mentioning
confidence: 99%
“…A posterior cervical discectomy was performed on 60 individuals, and an amniotomy or discectomy was performed on 18 patients (specific procedure per patient not reported). In RCTs, only 95 of 200+ MIS patients (42%) employed an anterior approach, compared to 190 of 200+ conventional open patients (88%) [ 3 , 4 ].…”
Section: The Following Issues May Arise Because Of Missmentioning
confidence: 99%
“…Both groups did not obtain fusion. Out of 500+ open patients, 500+ got discectomy, and 19 had percutaneous nucleosome, with the follow-up durations of 50–100 weeks (about 2 years) [ 4 6 ].…”
Section: The Following Issues May Arise Because Of Missmentioning
confidence: 99%